RETROSPECTIVE ANALYSIS OF PEDIATRIC HYDROCEPHALUS PATIENTS TREATED WITH ENDOSCOPIC THIRD VENTRICULOSTOMY - Tuğrul Cem Ünal; Duran Şahin; İlyas Dolaş; Duygu Dölen; Sefa Öztürk; Yavuz Aras; Aydın Aydoseli; Pulat Akın Sabancı; Altay Sencer (İstanbul Tıp Fakültesi Dergisi)
Objective: Ventriculoperitoneal (VP) shunt and endoscopic third ventriculostomy (ETV) are commonly utilized surgical interventions for managing hydrocephalus. This study aimed to analyze ETV procedures performed on patients under 17 years of age, focusing on demographic factors such as age and gender, etiological considerations, surgical complications, and the necessity for VP shunt placement. Material and Method: A retrospective review was conducted on pediatric patients who underwent ETV for hydrocephalus at the Department of Neurosurgery, Istanbul Faculty of Medicine, Istanbul University, spanning from January 2015 to June 2022. The study encompassed 44 patients aged 17 years or younger, with assessments made retrospectively based on clinical and radiological outcomes. Result: Among the 44 patients subjected to ETV for hydrocephalus, 24 were female (54.5%) and 20 were male (45.4%), with a mean age of 7.3 years. The most prevalent presenting symptom was headache, reported by 11 patients (25%), followed by increased head circumference in 10 patients (22.7%). The primary etiology of hydrocephalus was intracranial tumors (34%). In five patients (11.3%), ETV was performed to address shunt malfunction following a prior VP shunt procedure. Regression of hydrocephalus occurred in 30 patients (68.1%), while 14 patients (31.8%) necessitated a subsequent VP shunt placement. Postoperative wound complications were documented in five patients (11.3%).Conclusion: ETV offers distinct advantages over traditional shunt surgery, including reduced complication risks and enhanced quality of life. Despite the influence of various factors on the success of ETV in pediatric cases, the procedure has demonstrated safety and efficacy in a significant number of patients in this demographic.